A membrane-free electrochemical reactor for efficient oxygen removal via gravity-assisted product self-separation - Peng Li; Xin Tang; Xin Zhou; Changming Zhao; Wanyu Shen; Yi Tan; Deming Li; Peng Jiang; Fangyao Zhou; Zhe Wang; Jun Tang; Guiqiang Li; et al. (Nature Communications)
Abstract Although electrochemical technologies offer vast industrial prospects, broader adoption—particularly in consumer applications—remains constrained by high costs and limited component lifespans. Here, we present a gravity-assisted, membrane-free electrochemical oxygen (O2) removal (EOR) reactor coupling oxygen reduction (ORR) and oxygen evolution (OER) reactions. Leveraging fluid mechanics insights, buoyant O2 bubbles ascend rapidly, achieving 95% product self-separation and eliminating the need for membranes or external circulation. To withstand high hydrostatic pressures and ensure a 10-year operational lifespan, we developed an integrative gas diffusion electrode (GDE) with ~85.5% conductivity and 80.2% gas permeability relative to conventional carbon paper, yet 2.2-fold higher mechanical strength and 30-fold greater stability. In a household refrigerator, our two-cell system boosts fresh-keeping capacity by 3.4-fold. Comprehensive economic analysis reveals a 22.6-fold increase in O2 removal per unit cost compared with ion-exchange membrane-based reactors, underscoring this design’s cost-effective, long-lived potential for diverse real-world applications.